2016
DOI: 10.12944/cwe.11.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Drip Irrigation Regimes and Lateral Spacing on Cumin Productivity

Abstract: Cumin is one of the important spice crops grown in arid and semi arid regions of India and is being adopted to cure some of the dreaded diseases. Determination of optimum water requirement which is function of soil crop and atmosphere is needed for achieving more profit and higher productivity per unit of water. Keeping in view, a field experiment was undertaken to access the conjugate impact of three irrigation regimes (0.6IW/ETc, 0.8IW/ETc and1.0IW/ETc) and three lateral spacing (0.60m, 0.70m and 0.80m) on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 3 publications
2
3
0
Order By: Relevance
“…Our results revealed that drip irrigation at 0.6 CPE (I 0.6 ) enhanced the plant height by 15% and 5.36% over surface irrigation at CPE of 0.8 and drip irrigation at 0.4 CPE, respectively. These results are in close agreement with the results of Kunapara et al [27], who reported that the highest plant height was observed at 0.8 Irrigation water/Crop evapotranspiration (IW/ETc) ratio. Drip irrigation significantly enhanced the number of branches per plant.…”
Section: Effect Of Drip Irrigation Levels On Cumin Plant Growth Yield-attributing Characteristics and Yieldsupporting
confidence: 93%
See 3 more Smart Citations
“…Our results revealed that drip irrigation at 0.6 CPE (I 0.6 ) enhanced the plant height by 15% and 5.36% over surface irrigation at CPE of 0.8 and drip irrigation at 0.4 CPE, respectively. These results are in close agreement with the results of Kunapara et al [27], who reported that the highest plant height was observed at 0.8 Irrigation water/Crop evapotranspiration (IW/ETc) ratio. Drip irrigation significantly enhanced the number of branches per plant.…”
Section: Effect Of Drip Irrigation Levels On Cumin Plant Growth Yield-attributing Characteristics and Yieldsupporting
confidence: 93%
“…In our present study, the highest pooled B:C ratio was 2.9, which was equal at both 0.6 IW/ETc and 0.8 IW/ETc. Our economic results are in close agreement with the study of Kunapara et al [27], who reported the highest B:C ratio (2.39) at 0.8 IW/ETc with a lateral spacing of 0.6 m in cumin. Jat et al [40] also found that drip irrigation at an IW/CPE ratio 0.8 with paired row planting, being at par with 0.8 IW/CPE ratio in normal row planting and 1.0 IW/CPE ratio in normal and paired row planting, recorded significantly higher net returns and a B:C ratio over 0.4 and 0.6 IW/CPE ratios with normal and paired row planting.…”
Section: Introductionsupporting
confidence: 93%
See 2 more Smart Citations
“…There was 46% saving in water and 10-12% increase in seed yield with drip irrigation method as compared to surface irrigation [11]. The use of micro sprinkler in irrigating cumin crop is discouraged because it requires more energy than a drip system [54]. In order to provide irrigation by micro-sprinkler system the optimum IW/CPE ratio should be 0.8 [35,97].…”
Section: Management Of Crop Input Constraintmentioning
confidence: 99%